THEORETICAL APPROACHES IN INTERNATIONAL RELATIONS: THE SOUTH AFRICAN MILITARY AS A FOREIGN POLICY INSTRUMENT - Olivier, Laetitia; Neethling, Theo; Vreÿ, Francois (Scientia Militaria - South African Journal of Military Studies, 2015)
The utility of theoretical approaches in international relations can be found in the fact that such approaches provide ‘lenses’ that can be applied to enhance our understanding of the social dynamics of the world we live in. Theoretical approaches are also instrumental in shaping perceptions of what matters in international politics as a social activity. At least indirectly, such approaches inform the choices made by decision-makers on foreign policy and related defence planning. The aim of this article is to revisit those theoretical approaches in international relations that underlie security studies, and to evaluate the relevance of the approaches with regard to a scholarly understanding of militaries and specifically their roles and functions in a foreign policy context. The latter pertains to militaries in general but also to the South African military in particular regarding its role and function as a foreign policy instrument of the South African government.